Structure and propagation of n-heptane/air premixed flame in low temperature ignition regime. (1st October 2020) - Zhong, Shenghui; Zhang, Fan; Jangi, Mehdi; Bai, Xue-Song; Yao, Mingfa; Peng, Zhijun
Highlights: Premixed n-heptane/air flame in low temperature ignition (LTI) regime is investigated. In LTI regime heat release zone is broader than in chemically frozen (CF) regime. Turbulent and laminar burning velocities are higher in LTI regime than in CF regime. Mechanisms of enhanced burning velocity in LTI regime are proposed. Differential diffusion is more important in LTI regime than in CF regime. Abstract: This paper presents a large eddy simulation of n-heptane/air turbulent premixed combustion in a reactor assisted turbulent slot (RATS) burner under different preheating conditions. N-heptane/air mixture at an equivalence ratio of 0.6, pressure of 1 atm and temperature of 600, 650 and 700 K is considered to investigate the effect of low temperature chemistry on turbulent burning velocities and flame regimes, including chemically frozen (CF) regime where the fuel/air mixture inside the burner is chemically frozen, low temperature ignition (LTI) regime where the fuel/air mixture inside the burner undergoes LTI reactions, and transition regime from CF to LTI. The results show that the flame in the LTI regime exhibits the highest turbulent burning velocity. Differential diffusion is found to play an important role in the LTI regime whereas it is less important in the CF regime. To investigate the effect of LTI reactions on the flame, a series of two-dimensional laminar flames are simulated, in which the effect of turbulence on the flames is eliminated. The results show that in the LTI regime, the laminar burning velocity is drastically enhanced and the heat release zone is broadened. Budget term analysis shows that the enhanced rate of production and diffusion towards the preheat zone of the flames and the smaller gradient of reactant mass fraction are the main reasons behind the increased laminar burning velocity in the LTI regime.